The community resources of Lingayen which can be utilized in social studies instruction in the Pangasinan Provincial High School - Lavarias, Gonzalo A. 1931- (s.n.], 1967)
The community resources of Lingayen, Pangasinan which can be utilized in the social studies instruction in the local schools, particularly in Pangasinan Provincial High School are assembled, analyzed, and appraised to put up a resource unit aimed towards a better understanding of the local community of Lingayen as well as towards the enrichment of the various social studies courses in the secondary school level.